Management of an Unilateral Maxillary Impacted Canine: A Case Report - Hidayati, Nasyrah (Journal of Case Reports in Dental Medicine, 2022)
Objective: Maxillary canines are one of the most common teeth that are impacted among orthodontic patients. The canines are important teeth because of their function, occlusion, and aesthetics. Meanwhile, the most frequent cases that can be found in Indonesia are missing mandibular first permanent molar. This case report is about orthodontic treatment in 18 years old female patient. Clinical examination showed unilateral maxillary impacted canine, mild anterior crowding, and missing unilateral mandibular first permanent molar. The aim of this treatment is to make an ideal occlusion, correct the position of the canine, mild anterior crowding, and replace the missing first molar of the mandibular with a denture. This case report describes the management of a unilateral maxillary impacted canine.Methods: The patient’s treatment was initiated by leveling and aligning the arch. An open coil spring was used to gain space between the lateral incisor and maxillary first premolar on the left side.Result: After the position of the canine was achieved, the treatment was carried out to achieve the finishing detailing and arch coordination. Partial dentures are then prescribed to replace the missing first molar of the mandibular.Conclusions: The Unilateral maxillary impacted canine is clinically challenging. Successful orthodontic treatment can be achieved with minimal side effects in proper biomechanical control, diagnosis, and right treatment planning and also important in terms of esthetics and function and requires a qualified experience of a number of clinicians